1,000 books to read before you die : a life-changing list - Mustich, James (Workman Publishing, 2018)
Encompassing fiction, poetry, science and science fiction, memoir, travel writing, biography, children's books, history, and more, 1,000 Books to Read Before You Die moves across cultures and through time to present an eclectic collection of titles, each described with the special enthusiasm readers summon when recommending a book to a friend.